2017
DOI: 10.1111/tpj.13725
|View full text |Cite
|
Sign up to set email alerts
|

A functional zeaxanthin epoxidase from red algae shedding light on the evolution of light‐harvesting carotenoids and the xanthophyll cycle in photosynthetic eukaryotes

Abstract: The epoxy-xanthophylls antheraxanthin and violaxanthin are key precursors of light-harvesting carotenoids and participate in the photoprotective xanthophyll cycle. Thus, the invention of zeaxanthin epoxidase (ZEP) catalyzing their formation from zeaxanthin has been a fundamental step in the evolution of photosynthetic eukaryotes. ZEP genes have only been found in Viridiplantae and chromalveolate algae with secondary plastids of red algal ancestry, suggesting that ZEP evolved in the Viridiplantae and spread to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 86 publications
0
41
0
Order By: Relevance
“…In the red algae Graciliaria gracilis or G. multipartite an absence of Vx was detected and Ax seems to be the only substrate which can be converted to Zx (Bertrand and Schoefs, 1999). Despite the ongoing uncertainties about the presence of a xanthophyll cycle in Rodophyta, a recent study has presented clear evidence that at least a Zx epoxidase, which is able to convert Zx to Ax, is present in the red algae (Dautermann and Lohr, 2017).…”
Section: Reaction Sequences and Xanthophyll Cycle Enzymesmentioning
confidence: 99%
“…In the red algae Graciliaria gracilis or G. multipartite an absence of Vx was detected and Ax seems to be the only substrate which can be converted to Zx (Bertrand and Schoefs, 1999). Despite the ongoing uncertainties about the presence of a xanthophyll cycle in Rodophyta, a recent study has presented clear evidence that at least a Zx epoxidase, which is able to convert Zx to Ax, is present in the red algae (Dautermann and Lohr, 2017).…”
Section: Reaction Sequences and Xanthophyll Cycle Enzymesmentioning
confidence: 99%
“…Therefore, we validated the predictions for VDL by also analyzing the VDE sequences from 17 chromalveolates and 4 green plants/algae, with the expected targeting elements for luminal localization predicted in all investigated proteins (data file S1). (27) led to a much lower accumulation of neoxanthin in tobacco leaves compared with luminal targeting (table S2), indicating a higher activity of the enzyme at the more acidic pH in the thylakoid lumen. In leaves transformed with PtVDL1, the concentration of 9′cisneoxanthin also increased significantly by about 26 mmol/ mol Chl a for lumentargeted PtVDL1 (P = 2 × 10 −7 ) and by about 16 mmol/mol Chl a for stromatargeted PtVDL1 (P = 3 × 10 −6 ), suggesting that part of the neoxanthin generated by PtVDL1 may have been converted to 9′cisneoxanthin by an endogenous enzyme ( Fig.…”
Section: An Algal Mutant Devoid Of Allenic Carotenoids Is Defective Imentioning
confidence: 99%
“…us/#/projects/104), and the Online Resource for Community Annota tion of Eukaryotes (http://bioinformatics.psb.ugent.be/orcae/) were searched with the BLAST tool (45) using the amino acid sequences of the VDE family members from P. tricornutum (17) as input. MMETSP mining, protein alignments, and phylogenetic analyses using maximum likelihood methods with bootstrapping were performed as previously described (27). Accessions of sequence data used for cloning of algal genes and for in silico analyses are compiled in data file S2.…”
Section: Data Mining and Sequence Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another DEM, MiR5368g-5p, was down-regulated in PTI and PTFI seedlings. miR5368g-5p was predicted to target ZEP, which is the key enzyme responsible for the accumulation of antheraxanthin and violaxanthin [66]. Yang, et al [67] reported that a high expression of ZEP increased the stored carotenoid pigments in transgenic tomato plants.…”
Section: A Mir156-mir160-mir5368 Cluster Regulates Leaf Yellowing In mentioning
confidence: 99%